Impact of early social housing on the play behavior of neonatal and post-weaning dairy calves - McKay, Ciara; Ellis, Kathryn; Haskell, Marie J.; Gladden, Nicola (Frontiers in Veterinary Science, 2025)
We aimed to assess the impact of early life housing and play experiences on neonatal and weaned calves play behavior. A total of 96 female dairy calves were recruited from four Scottish dairy farms and assigned to individual (n = 48), paired (n = 24) or group (n = 24) housing at birth. Play behavior was measured using IceTag accelerometers (Peacock Technology, UK) during two experimental periods in the same cohort of calves, at neonatal and weaned stages. A mixed-effects negative binomial regression analysis was used to assess how early social housing influences the play behavior of neonatal and weaned calves. The analysis also considered the impact of early play on the play behavior of weaned calves. Calves housed in paired or group pens from birth performed significantly more neonatal play compared to calves housed individually from birth. No lasting effect of early life housing on weaned calf play behavior was observed. There was no correlation between counts of neonatal and weaned calf play. Calves with lower neonatal playfulness showed a numerical increase in play behavior after weaning compared to those with higher neonatal playfulness. These findings add to the growing body of literature indicating that early life social housing provides a more positive welfare experience for pre-weaned dairy calves. The study also highlights the need for future research to understand the impact of rearing experiences and different management systems on play behavior in weaned calves.